Argyrophilic nucleolar organiser region counts and prognosis in pharyngeal carcinoma. - Pich, A. (Nature Publishing Group, 1991)
The prognostic significance of argyrophilic nucleolar organiser regions (AgNORs) has been evaluated in biopsy specimens from 61 primary squamous and undifferentiated carcinomas of the pharynx prior to therapy. The univariate Kaplan-Meyer survival analysis showed a significant correlation between 3- and 5-year survival rates and the mean AgNOR number per tumour cell (P less than 0.001). No significant correlation was found between prognosis and patients age and sex, tumour location, clinical stage, histologic grade, extent of lymphocytic infiltration, HMFG-2 positivity of tumour cells and UCHL1, LN2, MB2 positivity of infiltrating lymphocytes. There was no significant association between AgNOR counts and tumour histologic grade or clinical stage. Multivariate survival analysis showed that only two variables were significantly correlated with prognosis: AgNOR counts (P less than 0.001) and the extent of lymphocytic infiltration (P less than 0.027). Our results indicate the prognostic value of AgNOR counts and suggest the use of this method as a significant parameter in the pretherapeutic assessment of the aggressiveness of pharyngeal carcinomas. IMAGES: